Rail-based urban transport - Sreedharan, E. (2001)
The phenomenal growth of urban population in the wake of industrialisation has put unprecedented strain on the road-based public transport in major towns and cities. Rail-based mass rapid transport system has been adopted by various countries at similar stage of development and urbanisation. Enumerating the advantages of MRTS over other modes of public transports, the article gives a detailed comparative study. It suggests possible roles of Centralo and state governments and Railways, while putting forward various technical and financial options in view of the limited resources and technical expertise. - Reproduced
Keywords: Railways; Transport; Urban transport